2012
DOI: 10.1121/1.4742138
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear ultrasound: Potential of the cross-correlation method for osseointegration monitoring

Abstract: Recently the concept of probing nonlinear elasticity at an interface prosthesis/bone has been proposed as a promising method to monitor the osseointegration/sealing of a prosthesis. However, the most suitable method to achieve this goal is a point of debate. To this purpose, two approaches termed the scaling subtraction method and the cross-correlation method are compared here. One nonlinear parameter derived from the cross-correlation method is as sensitive as a clinical device based on linear elasticity meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Albeit for acompletely different application, the above results are also found to be in line with astudy reported by Rivière et al on osseointegration monitoring [32]. In this study,the authors compared the sensitivity of three parameter dependencies, namely the correlation coefficient, the time delay and the energy of the SSM signal as function of input excitation levels, to probe the nonlinearity at an interface between ap rosthesis and the bone.…”
Section: Amplitude-dependent Response Of the Nsdc In Ac Omposite Cont...supporting
confidence: 88%
“…Albeit for acompletely different application, the above results are also found to be in line with astudy reported by Rivière et al on osseointegration monitoring [32]. In this study,the authors compared the sensitivity of three parameter dependencies, namely the correlation coefficient, the time delay and the energy of the SSM signal as function of input excitation levels, to probe the nonlinearity at an interface between ap rosthesis and the bone.…”
Section: Amplitude-dependent Response Of the Nsdc In Ac Omposite Cont...supporting
confidence: 88%
“…8 The softening of the material is evaluated as the relative velocity change Dc/c 0 with c 0 being the low amplitude speed of sound. The time delay Dt between signals is estimated by the cross-correlation of the low amplitude signal with higher amplitudes ones, similarly to the methods used by Rivière et al 11 and Tournat and Gusev, 12 for assessing nonlinearity. For more accuracy, the maximum position of the cross correlation is obtained by fitting the peak region with an oversampled second order polynomial function.…”
mentioning
confidence: 99%
“…In probing nonlinear elasticity at an interface prosthesis/bone as a promising method to monitor the osseointegration/sealing of prosthesis, cross-correlation-based methods are more sensitive than those based on subtraction/addition such like pulse inversion method. [65]. Pulse inversion technique is an ultrasonic nonlinear imaging technique that produces a better image contrast [66].…”
Section: Cross-correlationmentioning
confidence: 99%